Financial performance analysis before and after initial public offering in consumer cyclical and consumer non-cyclical sector companies on the indonesia stock exchange - Tri Wiyono Kurnianto; Malini, Helma; Wendy, Wendy; Giriati, Giriati; Setiawan, Harry (SEAN Institute, 2024)
This study aims to ascertain whether the financial performance of companies in the Consumer cyclical and Consumer non-cyclical sectors on the Indonesian stock exchange differs before and after their initial public offerings (IPOs). It is quantitative research. The population of this study is the Consumer Cyclical and Consumer Non-Cyclical sector companies that made initial public offerings (IPO) in 2019 – 2021. The sample in this study amounted to 54 companies using purposive sampling technique. The variables used are Current Ratio (CR), Return on Investment (ROI), Return on Equity (ROE), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO). Hypothesis testing uses paired sample t-test on normally distributed data and Wilcoxon signed ranks test on non-normally distributed data. The results obtained show that there are significant differences in CR, ROI, ROE, DAR, DER, and TATO between before and after the initial public offering (IPO).